Implementing a national first-line management program for moderate-severe knee osteoarthritis in Australia: A budget impact analysis focusing on knee replacement avoidance. Issue 3 (September 2020) - Ackerman, Ilana N.; Skou, Søren T.; Roos, Ewa M.; Barton, Christian J.; Kemp, Joanne L.; Crossley, Kay M.; Liew, Danny; Ademi, Zanfina
Summary: Objective: To model potential cost savings associated with implementing a first-line management program for moderate-severe knee osteoarthritis (OA) at a national level in Australia. Methods: A budget impact analysis was undertaken using published trial data and publically available data. Australian population projections and OA prevalence data were used to forecast likely need for total knee replacement (TKR) surgery for 2019–2029. Published data were sourced on TKR avoidance following a 12-week non-surgical knee OA management program (exercise therapy, education, insoles, dietary advice, analgesia) and cost per TKR in Australia. The cost of providing the first-line program was estimated on a sliding scale ($AUD750-$3000), with a base case of $AUD1, 500. These inputs were used to model potential annual savings associated with national implementation of the program. Results: The number of people in Australia with moderate-severe knee OA requiring TKR was estimated to be 56, 007 in 2019, rising to 69, 038 by 2029. Avoidance of TKR by 34%–68% of people after the first-line management program could translate to savings of $AUD303million-690 million in 2019. Successively lowering the proportion of people who avoided TKR demonstrated that only 1 in 12 program recipients would need to avoid surgery for the program to generate savings. Conclusions: National implementation of a first-line OA management program as an alternative to TKR could produce substantial cost savings for the Australian healthcare system. Longer term data on TKR avoidance is needed to establish whether cost savings are realised or simply shifted to later years.